Unveiling the defensive role of Snakin‑3, a member of the subfamily III of Snakin/GASA peptides in potatoes - Nahirñak, Vanesa; Almasia, Natalia Ines; Lia, Veronica Viviana; Hopp, Horacio Esteban; Vazquez Rovere, Cecilia (Springer, 2024)
Snakin/GASA proteins share 12 cysteines in conserved positions in the C-terminal region. Most of them were involved in different aspects of plant growth and development, while a small number of these peptides were reported to have antimicrobial activity or participate in abiotic stress tolerance. In potato, 18 Snakin/GASA genes were identified and classified into three groups based on phylogenetic analysis. Snakin-1 and Snakin-2 are members of subfamilies I and II, respectively, and were reported to be implicated not only in defense against pathogens but also in plant development. In this work, we present the first in-depth characterization of Snakin-3, a member of the subfamily III within the Snakin/GASA gene family of potato. Transient co-expression of Snakin-3 fused to the green fluorescent protein and organelle markers revealed that it is located in the endoplasmic reticulum. Furthermore, expression analyses via pSnakin-3::GUS transgenic plants showed GUS staining mainly in roots and vascular tissues of the stem. Moreover, GUS expression levels were increased after inoculation with Pseudomonas syringae pv. tabaci or Pectobacterium carotovorum subsp. carotovorum and also after auxin treatment mainly in roots and stems. To gain further insights into the function of Snakin-3 in planta, potato overexpressing lines were challenged against P. carotovorum subsp. carotovorum showing enhanced tolerance to this bacterial pathogen. In sum, here we report the first functional characterization of a Snakin/GASA gene from subfamily III in Solanaceae. Our findings provide experimental evidence on promoter activity and subcellular localization and reveal a role of potato Snakin-3 in plant defense.